Visible Near-Infrared Reflectance Spectroscopy Determination of Some Chemical Characteristics of Different Particular Sizes in Soils - Senol, H.; Akgul, M.; Mujdeci, M.; Basayigit, L. (Asian Journal of Chemistry, 2013)
The main objective of this study is to evaluate the ability of visible near-infrared reflectance spectroscopy (VNIRS) to predict diverse soil chemical properties in grinding different particular size effect. In this study, 60 soil samples were collected from the fields with serial classification (entisols, inceptisols, vertisols and mollisols) in Isparta (Atabey) district and crushed samples were subjected into five different mesh sizes (4.76-2.00, 2.00-1.00, 1.00-0.50, 0.5-0.25 and < 0.25 mm, respectively). Each soil samples were scanned with a visible near-infrared spectrometer, with a spectral range of 350 to 2500 nm, at five different particular sizes. The spectral reflectance's were used to predict some chemical properties of the soil (lime, sum of organic matter, cation exchange capacity, exchangeable calcium + magnesium, exchangeable potassium, exchangeable sodium) using partial least squares regression. Partial least squares analysis was used to develop calibration models between smoothed-first derivative 6 nm spaced spectral reflectance data and soil chemical analysis measured lime, sum of organic matter, cation exchange capacity, exchangeable calcium + magnesium, exchangeable potassium, exchangeable sodium. The results showed that while soils need to be crushed to pass through 0.25 mm sieve in order to determine exchangeable calcium + magnesium, exchangeable sodium, mesh size was found non-significant in determining lime, sum of organic matter, cation exchange capacity, exchangeable potassium and the results obtained from the reflectance values taken from field samplings proved to be satisfactory.